ETHNOBOTANICAL AND PHYTOPHARMACOLOGICAL REVIEW OF PISONIA ALBA SPAN - V, Tamizhazhagan; Pugazhendy K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Pisonia alba is used for the long period in various chronic diseases in traditional medicine use. To desire of this review is to search literature for the pharmacological properties toxicity studies, pharmacology studies and phytochemical exploration of anti-inflammation, antidiabetic studies,antioxidant, etc., and the amassed data may be helpful for the researchers to attention on the significance areas of research yet to be revealed. Widespread information about the plant has been together from various books, journals and ayurvedic classical texts, etc. Researcher and pharmacologist and Ayurveda treatment may be helpful security of the whole plant was settled in the criticism. Â Â Â